Law, reason, and emotion / edited by M. N. S. Sellers. - Sellers, Mortimer, 1959- (IVR studies in the philosophy of law and social philosophy, 2017)
This book examines the role and importance of reason and emotion in justice and the law. Eight lawyers and philosophers of law consider law's basis in the universal human need for society, our innate sense of justice, and many other powerful inclinations and emotions, including the desire for fairness and even for law itself. Human beings are deeply social creatures, inspired by social and other emotions, which can ennoble, support, or undermine the law. Law gains legitimacy and effectiveness when reason recognizes and embraces human emotions for the benefit of society as a whole. This volume explores the power and purposes of reason and emotion in the law.